Human anatomy and physiology - Crouch, James E.; McClintic, Joshep Robert (John Wiley & Sons, 1971)
A textbook treatment of human development, body structure and functioning, and elementary pathology that indicates the mechanisms serving to maintain homeostasis
Subject Index 629-646p.
Keywords: Human Anatomy; Physiology